Analisis tentang Pembaharuan Hukum Perwakafan - Yasir, Yasir (Jurnal Aplikasi Manajemen, 2009)
One of the strategic steps to improve social welfare of the ummah based on Islamic syaria is by improving the role of wakaf. As a religious institution, wakaf should not only be viewed as a means of transcendental worship and social devotion, but also an economic potency for the advance of general welfare. There is recognition towards the existence of general law as well as a clear reference to the principles of the the wakaf law. Thus, the management and the expediency of the law need a concrete and clear regulation. Based on the philosophy of expediency of the wakaf land (the land donated for religious or community use on given for public purpose) in Indonesia, Act No, 41, 2004 and Government Regulation number 42, 2006 implementation of Act No. 41, 2004 about the Wakaf has accommodated three law systems: Islam, customary, and western (secular) at once. As a part of Islamic jurisprudence, the law of wakaf is considered as ijtihadiyah and is accommodative on many opinions developed by Islamic schools (madzhab). The disposition of Act 41 Year 2004 and government Regulation No. 42 Year 2006 had given place for someone or law institutions to carry out the organization, management, and empowerment of wakaf based on Islamic syariah along with law assurance in the unitary state Republic of Indonesia.